PERANCANGAN JOB PROFILE BERBASIS SPREADSHEETS - Marco Hadi Surya; Albertus Daru Dewantoro (Industrial & System Engineering Journals (ISEJOU), 2022)
The most important asset a company needs is the role of humans. Without the human role, the company will not run as it should. Human resource management will be easy if it has rules. Rules and objectives will be given each entry into the organization for the first time. Therefore, using a Job Profile will provide responsibilities that should be owned by every employee so that work goals are clear and focused. PT X already has a Job Profile but it's still not as expected. All data is still done manually with the help of Ms Word. The research method used is a case study exploratory research. Primary data was collected by interviewing the recruitment and HRD. The secondary data obtained is the existing Job Profile at PT X, namely in the form of soft files and hard files. The results of this study will make it easier for recruitment parties to create Job Profiles automatically using spreadsheets. There are limitations to be used as report material because the Job Profile is confidential data owned by the company. Topics that can be used as reports are Job Title, Job Description, Job Specification, and Job Competency.